2019
DOI: 10.7717/peerj.7113
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic and biochemical characterization of a new model of the transition of acute kidney injury to chronic kidney disease induced by folic acid

Abstract: Background Renal diseases represent a major public health problem. The demonstration that maladaptive repair of acute kidney injury (AKI) can lead to the development of chronic kidney disease (CKD) and end-stage renal disease has generated interest in studying the pathophysiological pathways involved. Animal models of AKI–CKD transition represent important tools to study this pathology. We hypothesized that the administration of multiple doses of folic acid (FA) would lead to a progressive loss of renal functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 70 publications
1
13
0
Order By: Relevance
“…55 Therefore, FA-induced kidney disease can cover AKI, CKD, and the AKI-CKD transition. 54 Additionally, as FA is water-soluble and the injection is intraperitoneal, the procedure of kidney disease induction is simple and straightforward, without the need for surgery. Importantly, FA-induced kidney disease can recapitulate the clinical symptoms of human kidney disease and the model is highly reproducible.…”
Section: Hi G H Dos E S Of Fa and Renal Inj U Rymentioning
confidence: 99%
See 1 more Smart Citation
“…55 Therefore, FA-induced kidney disease can cover AKI, CKD, and the AKI-CKD transition. 54 Additionally, as FA is water-soluble and the injection is intraperitoneal, the procedure of kidney disease induction is simple and straightforward, without the need for surgery. Importantly, FA-induced kidney disease can recapitulate the clinical symptoms of human kidney disease and the model is highly reproducible.…”
Section: Hi G H Dos E S Of Fa and Renal Inj U Rymentioning
confidence: 99%
“…Nonetheless, for a given age group of the same gender in a particular animal species, data may be comparable. For example, in the same lab setting, if every experimental condition is strictly followed, the severity of kidney disease induced by a single injection of FA may be classified based on BUN content as: mild, 40–80 mg/dl; moderate, 100–200 mg/dl; severe, greater than 200 mg/dl 54 . The values shown in the Table for blood BUN and creatinine as well as GFR, if any, are for reference only as these numbers may vary from investigator to investigator.…”
Section: Introductionmentioning
confidence: 99%
“…It is an independent risk factor for cardiovascular disease and one of the causes of premature mortality. Moreover, the majority of the CKD cases is asymptomatic and not diagnosed until late stages, with limited therapeutic options available [1,2]. The state-of-the-art metabolomics technologies are considered as one of the most powerful analytical approaches with a big impact on the understanding of the molecular changes and pathogenesis of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Since Cr concentration is susceptible to age, gender, race, and diet, which may lead to overestimated glomerular ltration rate (GFR), CysC contains potential advantages as an indicator of renal function as compared to Cr. Serum urea nitrogen (UN) is also of great signi cance in early diagnosis of kidney diseases [13,14]. In present study, we recruited 14,716 subjects from the Health Examination Center at West China Hospital, Sichuan University, and analyzed the annual renal function indicators from 2012 to 2018, including UA, CysC, Cr and UN, to reveal distribution characteristics of renal function level in the population.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the cost of treatment for kidney diseases and related complications is a heavy nancial burden on health services around the world. Annual survey revealed that CKD cost about $35,000 to $100,000 per person per year [7,8]. In developing countries, due to infection, hazardous work and insu cient education, CKD poses a greater economic burden [6].…”
Section: Introductionmentioning
confidence: 99%